NFM-13. LONG TERM FOLLOW-UP OF OPTIC PATHWAY GLIOMAS IN CHILDREN WITH NEUROFIBROMATOSIS TYPE 1 – AN ONCOLOGY HOSPITAL EXPERIENCE. Issue 2 (22nd June 2018) - Fernandes, Mariana; Passos, João; Garcez, Daniela; Mafra, Manuela; Campos, Maria Fátima; Nunes, Sofia; Salgado, Duarte
Abstract: BACKGROUND: Optic Pathway Gliomas (OPGs) are the most prevalent intracranial tumours in children with Neurofibromatosis type 1 (NF1). Although commonly indolent, OPGs may have an aggressive clinical course and their approach is often challenging. The aim of this study was to evaluate the outcome of OPGs diagnosed in patients with NF1 during childhood, followed up to 22 years. METHODS: Retrospective review of demographics, neurological and ophthalmological evaluations, neuroimaging and treatments applied to all children with OPGs and NF1 presenting to an oncology hospital, 1991-2017. RESULTS: Of 62 children (31 males, 31 females, median age at diagnosis 4, 0 years), 27(44%) were treated (based on clinical or imagiological progression), in 4 off which the initial decision had been watchful surveillance. Of the treated patients, all were submitted to chemotherapy, 4 underwent surgery, 1 radiotherapy. Visual acuity improved in 9, stabilized in 12 and worsened in 3. Complete response was obtained in 1 patient, partial response in 19 and disease stability in 6. One patient died. One patient is currently under treatment, the remaining 25 have stable disease. Patients who didn't undergo treatment remain neuro-ophthalmologically stable, 2 had spontaneous tumour regression. Mean follow up time is 7, 9 years. CONCLUSION: Despite the complex management of patients with NF1 and OPGs, inherent to their variable natural history and difficulties in clearly defining neuro-ophthalmological progression and response to treatment in the pediatric population, our results suggest that careful surveillance is acceptable in most patients and that a majority of patients who undergo treatment benefit from it.